Optimization of strategies of development of the distributed production systems on the base of aggregating production functions - Borovska, T. M.; Kolesnyk, I. S.; Severilov, V. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Offered a) new raising of variation task of optimum development of the production system taking into account the use of external resources — without the increase of number of variables of management, b) method of aggregating of functions of development of elements in the optimum function of development of the production system. It enables to take the tasks of high dimension to single dimension. The developed programs of optimization and modeling of development processes allow building the system for technological prognostication in innovations.